Reproductive Biology and Larval Rearing of Blue Swimming Crab, Portunus Pelagicus (Linnaeus, 1758) - J. Halawa, Efrizal (2006)
Portunus pelagicus broodstock caught from the coastal region of Port Dickson, Negeri Sembilan, Malaysia in August 2004, and conditioned in the Hatchery Unit of Marine Research Station, UPM were used for the reproductive experiments including larval rearing studies. Various aspects of the reproductive biology of blue swimming crab, P. pelagicus were studied. Generally, sexual dimorphism and reproductive system of male and female blue swimming crab were observed to be similar to most other decapods crustaceans. The pubertal molt, the abdominal and gonopores structures of the female showed changes that are generally accepted as external morphological indications of sexual maturity. Unlike the female, the male showed pre-pubertal (loss of the attachment of the abdominal flap to the cephalothorax) rather than pubertal molt. The ovaries and testes were classified into five and three development stages respectively, and the ovarian histology of each stage was characterized. The ovarian stages correlated closely with the gonadosomatic index (GSI), the characteristics of ovarian histology and oviposition period. Fecundity estimates ranged from 148,897 to 835,401 eggs with brood size highly correlated to carapace width (CW), carapace length (CL), body weight (BW) and egg batch weight (EBW). The complete embryonic development of the blue swimming crab, P. pelagicus was described based on morphological features observed in live eggs. Periods of development were defined in sequence of 12 to 24 hours each and in relation to the time of embryonic development. Eight periods were described and illustrated for P. pelagicus. Embryonic development from recently spawned eggs (egg-mass appeared yellow and compact) to hatching lasted 8 days at 28-30oC. The larval stages included four zoeal stages and one megalopa. The megalopa molted to the first crab instar. The zoeae and megalopa were very similar to those of other portunids. The first and the second zoeal stages spanned 3-4 days each, the third and fourth stages were 2-3 days each, and the megalopa was 3-4 days. The first crab instar emerged 15- 18 days after hatching.